Fertirrigação na cultura da rúcula (Eruca Sativa MILLER) conduzida em ambiente protegido - Oliveira, Jhonatan Monteiro de (2013)
Fertigation is the application of fertilizers through irrigation water. This technique provides increased efficiency and split fertilization according to crops absorption, ease fertilizer incorporation, saving labor and energy, resulting in significant cost reduction of the production system. This study aimed to evaluate the effects of nitrogen and potassium applied by fertigation upon rocket salad cv. Folha Larga production, as well as to adjust and validate models in order to estimate leaf area based on linear leaves. The experiment was conducted in a greenhouse at the Technical Center of Irrigation (CTI) from the Department of Agronomy, University of Maringá. The experimental design was a completely randomized 4x4 factorial arrangement with three replications, which the treatments consisted of combinations of N (0, 60 , 120 and 240 kg ha - 1 ) and K ( 0 , 15 , 30 and 60 kg ha - 1 ) rates. Drip system was used in order to apply water and fertilizers in the rocket salad crop. Analyzed variables were marketable fresh weight per square meter (MFC), total dry weight per square meter (MST) and number of marketable leaves per plant (NFC) . In the adjustment of the models for estimating leaf area, leaves length (L) and width (L) were used as independent variables and leaf area measured by the method of digital image as the dependent variable. The A model was adjusted by the multiplication of length to width (L * C); B model was based on length (L); C model used the width (L) and D model used squared length (C²). The adjustment was made by the method of selection of models and Backward validation was performed using the correlation coefficient (r), the index of agreement (d), the performance index (c), the graphical analysis of leaf area estimated as a function of leaf area measurement , regression analysis of the error and graphical analysis of the error from models as a function of estimated leaf area . Nitrogen rates applied by fertigation promoted quadratic polynomial adjustment to the MFC when combined with levels 0 and 60 kg ha - 1 K, which also occurred for the variable MST when combined with the level 60 kg ha - one. The K promoted quadratic polynomial adjustment for the MFC when combined with the N level 240 kg ha - one. For the variable NFC, Potassium rates presented influence when analyzed separately and the values of the variable depending on the doses were adjusted on a crescent linear regression model. Considering the estimation of leaf area, all adjusted models e performance recognized as good (c > 0.85). However, from the graphical analysis and the regression model errors, only model A exhibited no systematic error and then the more recommended for the estimation of leaf area in the crop of rocket salad cv. Folha Larga.